2021
DOI: 10.1155/2021/6597402
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Antimigration Activity of Etlingera alba (A.D.) Poulsen Rhizome

Abstract: Etlingera alba is one of the Etlingera plants that might have anticancer activity. This study aims to investigate the cytotoxic and antimetastatic activity of E. alba rhizome fractions and migration cell assay against MDA-MB-231 cell lines, which are used for triple-negative breast cancer (TNBC) treatment assay. The cytotoxic activity was assayed using CCK-8 assay, while the antimetastatic was assayed using migration cell assay for the fractions A–F. They were followed by LCMS/MS profiling to determine the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
1
Order By: Relevance
“…Phenol (Ar-OH) is known to reduce the rate of oxidation of organic compounds by transferring the H atom (from its OH group) to the DPPH radical to become DPPH-H (Kamal et al 2022;Warsito et al 2022). Phenol also suppresses the formation of ROS so that damage caused by free radicals can be avoided (Wahyuni et al 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…Phenol (Ar-OH) is known to reduce the rate of oxidation of organic compounds by transferring the H atom (from its OH group) to the DPPH radical to become DPPH-H (Kamal et al 2022;Warsito et al 2022). Phenol also suppresses the formation of ROS so that damage caused by free radicals can be avoided (Wahyuni et al 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…The antitumor effects of rhamnazin were also proved in hepatocellular carcinoma [ 28 ]. Wahyuni et al thought spinasterol might have activity against cancer cells in triple-negative breast cancer [ 29 ]. Ravikumar et al reported the antiproliferative and proapoptotic activities of spinasterol [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian selanjutnya yaitu ekstrak metanol batang E. rubroloba aktif sebagai antioksidan (Jabbar et al, 2021a) dan menghambat xantin oksidase (Jabbar et al, 2021b), ekstrak etanol buah E rubroloba aktif sebagai imunomodulator (Ilyas et al, 2021). Rimpang E. alba aktif sebagai antioksidan dan mengandung senyawa alkaloid, flavonoid, terpenoid, steroid (Wahyuni et al,2021), ekstrak rimpang E. alba aktif sebagai antiinflamasi (Hamsidi et al,2021). Selanjutnya Etlingera pubescens mengandung senyawa etlingerin dan menunjukkan aktivitas sebagai antibakteri dan sitotoksik yang lebih baik dibandingkan dengan kurkumin (Jambun et al, 2019), kemudian E. brevilabrum aktif sebagai penurunan kolesterol (Mahdavi, 2014), E. coccinea dan E. sessilanthera aktif sebagai antibakteri (Jambun et al, 2017).…”
Section: Pendahuluanunclassified